PLURALISME AGAMA DI DESA BALUN LAMONGAN DITINJAU DARI PRESPEKTIF HADIS - Amiruddin, Wildan; A.W, Liliek Channa (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
Pluralism is an appreciation of one’s profound awareness of difference. This realization would lead him to the next level of stability and away from violence. Pluralism is a term that can be applied to people of this nature in Indonesia, given their racial, cultural, and religious diversity. Balun village in the Lamongan District is one of the villages in Indonesia that is conscious of religious pluralism. The village is home to a variety of religious groups. Three religions coexist peacefully in the village, namely Islam, Christianity, and Hinduism. While the word pluralism originated in the west, the Prophet exemplified the concept in many hadiths, especisally concerning religious pluralism that can still be traced (takhrīj) to the facts. Thus, this study would be important to read due to its unique approach, which is based on hadith.